THE EFFECT OF RADIATION PROTECTION ON THE DEVELOPMENT OF THYROID NODULES AMONG RADIOGRAPHERS IN MALANG - Aisy, Rahmi Mufidah; Aurora, Habiba; Karliasari, Liana (Department of Radiology, Medical Faculty, University of Brawijaya, 2023)
The use of radiation technology in Indonesia is mostly applied in the medical world and is immensely beneficial, but radiation exposure also has negative effects on health in the form of deterministic and stochastic effects. The thyroid gland is at a high risk of radiation exposure, which leads to the development of thyroid nodules. To prevent that, there must be safety measures in the use of radiation technology by implementing radiation protection, such as a thyroid shield. This study aims to examine the effect of the compliant use of a thyroid shield on the development of thyroid nodules among radiographers in Malang. This study is an observational study with the use of secondary data, where the primary data were previously gathered cross-sectionally in April 2021. The data from 40 subjects were then analyzed using a T-test with the result of the t-value = 4.299 and α = 0.000. With the result of α < 0.05 and t-value > t-distribution, this study concludes that the use of a thyroid shield has an effect on the development of thyroid nodules among radiographers in Malang, and compliant use can lower the incidence of thyroid nodules. Keywords: Radiation exposure, radiographer, thyroid nodule, thyroid